2011
DOI: 10.1007/s00221-011-2723-y
|View full text |Cite
|
Sign up to set email alerts
|

It is all me: the effect of viewpoint on visual–vestibular recalibration

Abstract: Participants performed a visual-vestibular motor recalibration task in virtual reality. The task consisted of keeping the extended arm and hand stable in space during a whole-body rotation induced by a robotic wheelchair. Performance was first quantified in a pre-test in which no visual feedback was available during the rotation. During the subsequent adaptation phase, optical flow resulting from body rotation was provided. This visual feedback was manipulated to create the illusion of a smaller rotational mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Eight studies were directed to investigate how participant's characteristics can influence the ownership illusion when using the RHI paradigm such as age, showing a preserved ability to integrate the perceptual illusion of the RH (Riemer et al, 2019;Zeller & Hullin, 2018); laterality, which even though some studies did not found differences in experiencing the RHI between left-handers and righthanders (Smit et al, 2017), others found a more vivid illusion when using the RHI in left-handers compared to right-handers (Ocklenburg et al, 2011) ; psychosis proneness, which foster the sense of ownership toward the rubber hand (Germine et al, 2013); non-clinical autism spectrum that could influence the perception of the rubber arm position (Palmer et al, 2013); or participants presenting some medically unexplained symptom, which presented lower RHI experience compared to a normal participants (Miles et al, 2011). Six studies aimed at investigating how by the manipulation of body sensory or cognitive components is possible to modulate the ownership illusion toward a body part (Dempsey-Jones & Kritikos, 2014;Ferrè et al, 2015;Lopez et al, 2010;Morgan et al, 2011;Ponzo et al, 2018;Schomaker et al, 2011). More specifically, three studies manipulated vestibular information in healthy subjects while performing the RHI paradigm (Ferrè et al, 2015;Lopez et al, 2010;Macauda et al, 2015;Ponzo et al, 2018), and one study during the VHI (Schomaker et al, 2011), and found that through the vestibular stimulation participant increased the sense of proprioceptive drift toward the fake body part enhancing the sense of ownership.…”
Section: Bi To Modulate Body Representation Evidence From Healthymentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were directed to investigate how participant's characteristics can influence the ownership illusion when using the RHI paradigm such as age, showing a preserved ability to integrate the perceptual illusion of the RH (Riemer et al, 2019;Zeller & Hullin, 2018); laterality, which even though some studies did not found differences in experiencing the RHI between left-handers and righthanders (Smit et al, 2017), others found a more vivid illusion when using the RHI in left-handers compared to right-handers (Ocklenburg et al, 2011) ; psychosis proneness, which foster the sense of ownership toward the rubber hand (Germine et al, 2013); non-clinical autism spectrum that could influence the perception of the rubber arm position (Palmer et al, 2013); or participants presenting some medically unexplained symptom, which presented lower RHI experience compared to a normal participants (Miles et al, 2011). Six studies aimed at investigating how by the manipulation of body sensory or cognitive components is possible to modulate the ownership illusion toward a body part (Dempsey-Jones & Kritikos, 2014;Ferrè et al, 2015;Lopez et al, 2010;Morgan et al, 2011;Ponzo et al, 2018;Schomaker et al, 2011). More specifically, three studies manipulated vestibular information in healthy subjects while performing the RHI paradigm (Ferrè et al, 2015;Lopez et al, 2010;Macauda et al, 2015;Ponzo et al, 2018), and one study during the VHI (Schomaker et al, 2011), and found that through the vestibular stimulation participant increased the sense of proprioceptive drift toward the fake body part enhancing the sense of ownership.…”
Section: Bi To Modulate Body Representation Evidence From Healthymentioning
confidence: 99%
“…Six studies aimed at investigating how by the manipulation of body sensory or cognitive components is possible to modulate the ownership illusion toward a body part (Dempsey-Jones & Kritikos, 2014;Ferrè et al, 2015;Lopez et al, 2010;Morgan et al, 2011;Ponzo et al, 2018;Schomaker et al, 2011). More specifically, three studies manipulated vestibular information in healthy subjects while performing the RHI paradigm (Ferrè et al, 2015;Lopez et al, 2010;Macauda et al, 2015;Ponzo et al, 2018), and one study during the VHI (Schomaker et al, 2011), and found that through the vestibular stimulation participant increased the sense of proprioceptive drift toward the fake body part enhancing the sense of ownership. One study investigated the effect of ketamine on the experience of illusory ownership toward the rubber hand, which mimics the perturbed sense of body ownership seen in schizophrenia enhancing the possibility to induce body illusions (Morgan et al, 2011).…”
Section: Bi To Modulate Body Representation Evidence From Healthymentioning
confidence: 99%
“…In particular, VR combines high realism and excellent experimental control 28 , so that the stimuli presented to the users can be manipulated or distorted in a perfectly controlled manner in order to suit speci c objectives 29 . A straightforward example of such manipulations is the ability to display a different perspective or viewpoint on the visual scene [30][31][32][33] . Because it 'breaks the laws of optics and physics', this type of manipulation would obviously not be possible using real-world settings.…”
Section: Introductionmentioning
confidence: 99%
“…Because it 'breaks the laws of optics and physics', this type of manipulation would obviously not be possible using real-world settings. In addition, feedback about performance, be it real-time or delayed, can be effortlessly and exibly augmented, manipulated or individualized to meet speci c needs or goals 32 . All these attributes make VR a unique tool to investigate human cognition and behavior 29 , as well as to develop e cient training protocols allowing people to learn or re-learn motor and cognitive skills [34][35][36][37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%